Aspectos clínicos, prognósticos e terapêuticos da corioretinopatia serosa central - Roisman, Luiz [UNIFESP] (2017)
Objective: to study clinical features, prognostic factors and therapeutic options of central serous chorioretinopathy. Methods: three studies were conducted. The first one, atransversal study, correlated findings of standard autofluorescence and near infrared autofluorescence with fluorescein angiography and optical coherence tomography changes. The second, a prospective study, the retinal microperimetry was tested as a prognostic factor to verify the risk of chronification of central serous chorioretinopathy, defined as subretinal fluid persistence at the end of three months of follow-up. The third was a prospective and randomized clinical trial that evaluated the efficacy of micropulse subthreshold laser therapy compared to sham laser photocoagulation in patients with chronic central serous chorioretinopathy. Results: In the first study, we found that diffuse hyperautofluorescence in standard autofluorescence is the most common sign in chronic central serous chorioretinopathy and the spot of leakage on fluorescein angiography is associated with focal changes on near infrared autofluorescence and with detachment of the retinal pigment epithelium on optical coherence tomography simultaneously. In the second study, we identified that the average of macular sensitivity measured with retinal microperimetry less than 20 dB at the beginning of the acute phase represented a 4.5 folds increase in the risk of chronification. Finally, the micropulsed laser was effective in the resolution of sub-retinal elevation, in the reduction of macular thickness and in the improvement of visual acuity in comparison to sham laser, with no clinically visible scars of photocoagulation and/or significant chorioretinal sequelae. Conclusion: autofluorescence images are useful in determining the spot of leakage with no intravenous contrast and also correlate with alterations of retinal pigment epithelium on optical coherence tomography. The average of macular sensitivity measured with retinal microperimetry may be useful in evaluating the prognosis in acute central serous chorioretinopathy. Micropulse laser was shown to be effective and safe in the treatment of chronic central serous chorioretinopathy in this case series